Electricity purchasing strategy for the regional power grid considering wind power accommodation. Issue 8 (2nd April 2018) - Yu, Simin; Wen, Buying; Wang, Liangyuan; Chen, Jing
Abstract : In this paper, a monthly power purchase optimization problem for regional power grid is studied. Considering the uncertainties of wind power and the effect of day‐ahead market, an optimal model of power purchase for regional power grid is built. The proposed model considers wind power in the monthly electricity balance, and it also realizes double‐risk management of over peak regulation and power purchase loss. 'SHARP ratio' in economics is introduced as an index of purchasing benefit–risk coordination. It can reflect the comprehensive benefits of electricity purchase visually. The monthly purchase scheme is refined to peak, flat and valley periods of every day, and the optimal purchasing quantity of thermal power, wind power and interregion power are obtained. The simulation results show that the risk preference has a significant impact on the purchase decision‐making. Reducing wind power forecasting error and the difference between load peak and valley is conducive to achieving a better comprehensive benefit of power purchase. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.